Estimating Benzathine Penicillin Need for the Treatment of Pregnant Women Diagnosed with Syphilis during Antenatal Care in High-Morbidity Countries. - Melanie M Taylor; Stephen Nurse-Findlay; Xiulei Zhang; Lisa Hedman; Mary L Kamb; Nathalie Broutet; James Kiarie (PLoS ONE)
Background Congenital syphilis continues to be a preventable cause of global stillbirth and neonatal morbidity and mortality. Shortages of injectable penicillin, the only recommended treatment for pregnant women and infants with syphilis, have been reported by high-morbidity countries. We sought to estimate current and projected annual needs for benzathine penicillin in antenatal care settings for 30 high morbidity countries that account for approximately 33% of the global burden of congenital syphilis. Methods Proportions of antenatal care attendance, syphilis screening coverage in pregnancy, syphilis prevalence among pregnant women, and adverse pregnancy outcomes due to untreated maternal syphilis reported to WHO were applied to 2012 birth estimates for 30 high syphilis burden countries to estimate current and projected benzathine penicillin need for prevention of congenital syphilis. Results Using current antenatal care syphilis screening coverage and seroprevalence, we estimated the total number of women requiring treatment with at least one injection of 2.4 MU of benzathine penicillin in these 30 countries to be 351,016. Syphilis screening coverage at or above 95% for all 30 countries would increase the number of women requiring treatment with benzathine penicillin to 712,030. Based on WHO management guidelines, 351,016 doses of weight-based benzathine penicillin would also be needed for the live-born infants of mothers who test positive and are treated for syphilis in pregnancy. Assuming availability of penicillin and provision of treatment for all mothers diagnosed with syphilis, an estimated 95,938 adverse birth outcomes overall would be prevented including 37,822 stillbirths, 15,814 neonatal deaths, and 34,088 other congenital syphilis cases. Conclusion Penicillin need for maternal and infant syphilis treatment is high among this group of syphilis burdened countries. Initiatives to ensure a stable and adequate supply of benzathine penicillin for treatment of maternal syphilis are important for congenital syphilis prevention, and will be increasingly critical in the future as more countries move toward elimination targets.